2019
DOI: 10.3389/fphar.2018.01495
|View full text |Cite
|
Sign up to set email alerts
|

GSK-3 Inhibitors and Tooth Repair: An Ethical Analysis

Abstract: Tideglusib®, a GSK-3 inhibitor, was initially tested for the treatment of Alzheimer’s disease. However, a recent report has suggested its potential off-label use for the treatment of dental cavities. Even if this effect is not yet confirmed, this off-label use can have significant public/dental health consequences, mainly because of the large number of patients with cavities. The purpose of this mini-review is to perform an ethical analysis of the use of Tideglusib in dentistry. The ethical analysis identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Most treatment-associated adverse events have been categorized as mild-to-moderate and have consisted of headache, diarrhea, cough, nausea, elevated liver transaminases (GGT and ALT) and creatine and fatigue. In a 2013 pilot study, and a phase II study in 2014 reported by del Ser et al and Lovestone, et al, respectively, these adverse events were significant enough to result in a dropout rate of more than one-third of those enrolled in the trial [126][127][128]. So far, most studies utilizing 9-ING-41 and Tideglusib have been focused on Alzheimer's or cancer, although a number of studies utilizing Tideglusib have recently gotten underway to evaluate its use in amyotrophic lateral sclerosis (ALS) and myotonic dystrophy (https://clinicaltrials.gov/ct2/results?…”
Section: Discussionmentioning
confidence: 95%
“…Most treatment-associated adverse events have been categorized as mild-to-moderate and have consisted of headache, diarrhea, cough, nausea, elevated liver transaminases (GGT and ALT) and creatine and fatigue. In a 2013 pilot study, and a phase II study in 2014 reported by del Ser et al and Lovestone, et al, respectively, these adverse events were significant enough to result in a dropout rate of more than one-third of those enrolled in the trial [126][127][128]. So far, most studies utilizing 9-ING-41 and Tideglusib have been focused on Alzheimer's or cancer, although a number of studies utilizing Tideglusib have recently gotten underway to evaluate its use in amyotrophic lateral sclerosis (ALS) and myotonic dystrophy (https://clinicaltrials.gov/ct2/results?…”
Section: Discussionmentioning
confidence: 95%
“…Further, it is desirable for the drug delivery system to have a higher drug loading capacity that reduces the number of delivery vehicles [31]. Hostiuc et al [32], in 2019, raised concern about the systemic action of tideglusib and its introduction to endodontics and restorative procedures. Intra-dental application of tideglusib could cause increased release time, which could potentiate a significant local effect.…”
Section: Discussionmentioning
confidence: 99%
“…1 Glycogen synthase kinase-3 inhibitor have been studied as a potential therapeutic agents in depression, anxiety, schizophrenia, Alzheimer's disease, supranuclear palsy, fragile X syndrome, multiple sclerosis, Parkinson's disease, Huntington's disease, stroke, traumatic brain injury, spinocerebellar ataxia type 1, sepsis, asthma, arthritis, colitis, peritonitis and various types of cancers. 2 These drugs have the capacity to modulate human stem cells in vivo. Tideglusib, a glycogen synthase kinase-3 inhibitor, initially tested for its role in Alzheimer's disease and psychiatric disorders, has the potential to change the conventional treatment of dental caries owing to its property to regrow dentine to fill a void.…”
mentioning
confidence: 99%